AI4Design: A generative AI-based system to improve creativity in design–A field evaluation - Luca Abrusci; Karma Dabaghi; Stefano D'Urso; Filippo Sciarrone (Computers and Education: Artificial Intelligence)
Chatbots serve as valuable instruments for enhancing students' educational experience and aiding them in their day-to-day academic tasks. Advances in Generative AI (GAI) have ushered in increasingly sophisticated and adaptive chatbots, with ChatGPT and DALL⋅E being prime examples. ChatGPT excels at generating text-based answers across diverse areas of knowledge, while DALL⋅E is adept at converting text-based concepts into visual imagery. These technologies are increasingly used by students across various levels of education. In this study, we introduce AI4Design, a web-based system designed to assist design students with their course projects by acting as an intelligent chatbot. The field of design is propitious for such work because of the increasing use of technology and the necessity of introducing its critical use during study. Comprising two integrated modules, the system is based on a two-step workflow. The first step is anchored on ChatGPT, enabling students to prompt questions and receive answers. The second step allows for the generation of one or more images based on the system's answer to the initial question. Our research assesses whether our system can offer valuable insights and inspiration to students in their design work. We conducted an exploratory study in the Design domain involving 31 students from the Lebanese American University. Over a two- to three-day period, participants used the AI4Design system to enhance their projects. A subsequent evaluation of their work indicated improvements in conceptual clarity and visual outputs that highlighted a measurable increase in creativity, supporting the efficacy of both the system and its foundational learning model, which will be confirmed in the future through a large-scale experimental study. Meanwhile, our study suggests that in the iterative design process, GAI can assist students in making better decisions by giving them just-in-time access to a broader palette of possibilities.